2000
DOI: 10.1161/01.cir.101.12.1403
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation After Coronary Artery Bypass Surgery

Abstract: A combination of prolonged SAPD, advanced age, and male sex identifies patients at high risk for development of AF after CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
246
8
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(282 citation statements)
references
References 45 publications
21
246
8
6
Order By: Relevance
“…For instance, Hogue and Hyder (1) observed that in addition to age, valvular heart operation is the most consistently identified risk factor for cardiac arrhythmia. Similar to the present results (age, ≥60 years; P<0.001), Zaman et al (6) found that advanced age is markedly associated with postoperative AF (65.9 vs. 61.7 years; P<0.0005). The frequency of this arrhythmia is increasing, possibly due to the rising proportions of elderly patients undergoing cardiac surgery.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For instance, Hogue and Hyder (1) observed that in addition to age, valvular heart operation is the most consistently identified risk factor for cardiac arrhythmia. Similar to the present results (age, ≥60 years; P<0.001), Zaman et al (6) found that advanced age is markedly associated with postoperative AF (65.9 vs. 61.7 years; P<0.0005). The frequency of this arrhythmia is increasing, possibly due to the rising proportions of elderly patients undergoing cardiac surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Postoperative AF (POAF) is frequently considered to be a temporary problem; however, this complication results in significant adverse effects. POAF increases the risk of a cerebrovascular accident, extending the duration of hospital stay and the requirement for intensive care (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the main risk factors contributing to the onset of this arrhythmia are: old age, male gender, valve disease, increased atrial size, previous arrhythmias, chronic obstructive pulmonary disease, previous cardiac surgery, discontinuation of betablockers, use of digoxin, ventricular dysfunction and anemia 11 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Although often transient and benign, AF after CABG prolongs hospital stay and may lead to complications such as hemodynamic instability or thromboembolic events. 2 The mechanism of AF after CABG is not well defined; however, animal studies as well as clinical case studies suggest that endogenous adenosine, released in response to tissue hypoxia, may play a mechanistic role in these arrhythmias. 3,4 It is postulated that endogenous adenosine, released during the surgical procedure, shortens the atrial action potential duration and effective refractory period.…”
Section: Introductionmentioning
confidence: 99%